Kontribusi Peradaban Islam terhadap Sains dan Teknologi: Refleksi untuk Masa Depan Digital - Samsul Bahri (Yayasan Albahriah Jamiah Indonesia, 2025)
Islamic civilization has made significant contributions to the development of technology and science, especially during the golden age of Islam, which was marked by the establishment of the Baitul Hikmah in Baghdad. This institution became a center for translation, the development of science, and innovation in various fields such as medicine, mathematics, astronomy, and engineering. However, over time, Islamic science’s dominance declined until Western dominance emerged in the Industrial Revolution. In the current era of the Industrial Revolution 4.0, there is a need to reflect and reintegrate Islamic scientific values and heritage in facing modern global challenges. This study aims to examine the traces of Islam’s contribution to science and technology and examine its relevance in the context of the current digital era. The method used is a qualitative study with a historical approach through a literature review of classical and contemporary literature. The results of the study show that Muslim scientists such as al-Khawarizmi, Ibn Sina, and al-Jazarī have laid the foundations of science that are references for Western scientists. In conclusion, the legacy of Islamic science not only has historical value but also the potential for actualization in the development of technology and science based on ethics, spirituality, and humanity in the era of the Industrial Revolution 4.0. Revitalizing Islamic scientific thought is the key to building a civilization that is balanced between technological progress and universal moral values.